Peningkatan Kemampuan Literasi Digital dan Hasil Belajar IPAS melalui Penerapan Model Problem Based Learning Berbantuan Media Interaktif pada Siswa Kelas V SDN 39 Cakranegara - Nindi Claudya; Darmiany; Siti Rahmatillah (Mataram University, 2026)
This classroom action research aimed to improve the digital literacy and learning outcomes in Science and Social Studies (IPAS) of fifth-grade students at SDN 39 Cakranegara through the implementation of the Problem-Based Learning (PBL) model assisted by interactive media. The study was conducted during the second semester of the 2025/2026 academic year using the Kemmis and McTaggart Classroom Action Research model, which consisted of two cycles. Each cycle comprised four stages: planning, action, observation, and reflection. The participants were 28 fifth-grade students, consisting of 14 boys and 14 girls. Data were collected through observations of teacher and student activities, learning achievement tests, and documentation. The findings indicated that the implementation of the Problem-Based Learning model assisted by interactive media significantly improved students' learning activities and learning outcomes. Classical learning mastery increased from 64.29% in Cycle I to 89.29% in Cycle II, exceeding the minimum success criterion of 85%. The mean student score also improved from 72.14 in Cycle I to 84.68 in Cycle II, surpassing the minimum criterion of 80. Student activity increased from 76% (good category) in Cycle I to 91% (very good category) in Cycle II. Furthermore, students demonstrated improved abilities to access, manage, and utilize digital information during the learning process, indicating enhanced digital literacy. These improvements occurred because the PBL model provided opportunities for students to engage actively in solving authentic problems, while the interactive media made learning more engaging and contextual. Therefore, the implementation of the Problem-Based Learning model assisted by interactive media was effective in improving digital literacy and learning outcomes in Science and Social Studies (IPAS) among fifth-grade students at SDN 39 Cakranegara. This model can serve as an innovative instructional alternative for enhancing the quality of learning in elementary schools.